PENGARUH PEMANFAATAN WHATSAPP TERHADAP INTERAKSI ANAK DAN ORANG TUA PESERTA DIDIK SMPN 10 PONTIANAK - Siti Aisyah; Muhammad Asrori; Yuline Yuline (Universitas Tanjungpura, 2018)
AbstractWhatsApp is an instant messaging app. By using WhatsApp, users can communicate anywhere and anytime with people who also have the application as long as it is connected to the internet network connection. WhatsApp's use of influence on child and parent interactions is crucial given the increasingly sophisticated development of many children affected by WhatsApp resulting in less interaction with parents. The method used is descriptive method and the form of research is a form of relationship studies. This research is a quantitative approach. Data collection techniques used are indirect communication techniques and data collection tools with questionnaires or questionnaires. While the technique of data analysis using the percentage formula. Based on the results of this study pengapug utilization of WhatsApp on the interaction of children and parents in students class VII SMP Negeri 10 Pontianak achieve score in the category of